The Application of the Principle of Professionalism by Notaries in the Preparation of Authentic Deeds: Penerapan Asas Profesionalitas Pada Notaris Dalam Pembuatan Akta Autentik - Tahta Fortuna Maharani Wijaya; Ery Agus Priyono (Universitas Islam Indonesia, 2024)
This study aims to analyze the application of the principle of professionalism to notaries in making authentic deeds. Authentic deeds are considered as deeds that are perfect evidence in the eyes of the law. In their services to the community, notaries must apply principles, one of which is the principle of professionalism. The principle of professionalism has an urgency to be applied by notaries, especially in making authentic deeds where with the principle of professionalism, the authentic deeds made will achieve the appropriate output. In this regard, this study has a problem formulation, namely